Hierarchical Acrylic Acid Aggregate Morphologies Produce Strain-Hardening in Precise Polyethylene-Based Copolymers (2015)
We report tensile testing and in situ X-ray scattering measurements of a homologous series of precise poly(ethylene-co-acrylic acid) copolymers (pxAA). The number of backbone carbons (x) between pendant acrylic acid groups along the polyethylene chain (x = 9, 15, 21) has a pronounced effect on both their tensile properties as well as their morphologies during deformation. The semicrystalline precise copolymer (p21AA) displays yielding behavior similar to polyethylene. Also, strain hardening in p21AA coincides with the originally isotropic acid-rich layered structures strongly aligning with acid layers perpendicular to the strain direction, demonstrating the facile nature of the H-bonding within the acid aggregates. When the alkyl spacer is only nine carbons (p9AA), the precise copolymer withstands strains of >1000% without failing, because the liquid-like assembly of acid aggregates permits the acid groups to exchange without developing substantial anisotropy in the structure. Both p21AA and p9AA maintain...